Dissociation of β2‐microglobulin determines the surface quality control of major histocompatibility complex class I molecules. Issue 7 (17th March 2015) - Montealegre, Sebastián; Venugopalan, Vaishnavi; Fritzsche, Susanne; Kulicke, Corinna; Hein, Zeynep; Springer, Sebastian
ABSTRACT: Major histocompatibility complex class I proteins, which present antigenic peptides to cytotoxic T lymphocytes at the surface of all nucleated cells, are endocytosed and destroyed rapidly once their peptide ligand has dissociated. The molecular mechanism of this cellular quality control process, which prevents rebinding of exogenous peptides and thus erroneous immune responses, is unknown. To identify the nature of the decisive step in endocytic sorting of class I molecules and its location, we have followed the removal of optimally and suboptimally peptide‐loaded murine H‐2K b class I proteins from the cell surface. We find that the binding of their light chain, β2 ‐microglobulin (β2 m), protects them from endocytic destruction. Thus, the extended survival of suboptimally loaded K b molecules at 25°C is attributed to decreased dissociation of β2 m. Because all forms of K b are constantly internalized but little β2 m‐receptive heavy chain is present at the cell surface, it is likely that β2 m dissociation and recognition of the heavy chain for lysosomal degradation take place in an endocytic compartment.—Montealegre, S., Venugopalan, V., Fritzsche, S., Kulicke, C., Hein, Z., Springer, S. Dissociation of β2 ‐microglobulin determines the surface quality control of major histocompatibility complex class I molecules. FASEB J . 29, 2780‐2788 (2015). www.fasebj.org